The Goldilocks challenge : right-fit evidence for the social sector - Gugerty, Mary Kay (Oxford University Press, 2018)
"The recent push for impact measurement has been positive, but it has also led to wasted resources and often misleading data about what works. In The Goldilocks Challenge, Gugerty and Karlan put forth four key principles to guide organizations of all sizes to create strong, "right-fit" data collection systems" --